Perbandingan Hasil Belajar Peserta Didik Menggunakan Problem Based Learning Dengan Contextual Teaching and Learning Dalam Pelajaran Geografi - Novia Zalmita; Novra Rizkia (JPIG (Jurnal Pendidikan dan Ilmu Geografi), 2020)
Teaching and learning practices today are often found problems such as the use of models that are still minimal and not in accordance with the characteristics of students. Generally teachers teach using only conventional learning models, while the Kurikulum 2013 requires students to be able to think at a high level. This can certainly be achieved by applying learning models such as Problem Based Learning and Contextual Teaching and Learning in the learning process. This study aims to compare the learning outcomes of the two models in Class X Geography in SMAN 5 Banda Aceh. The research method uses a quantitative approach to the type of experimental research that is quasi-experimental design with the initial assumption that learning outcomes taught using Problem Based Learning are better than those taught using Contextual Teaching and Learning. The population in this study were all grade X students at SMAN 5 Banda Aceh. Sampling using a purposive sampling by considering the initial ability of students is the same. Samples were taken as many as two classes totaling 46 students. Hypothesis testing techniques using non-parametric statistical tests according to Mann-Whitney (U test) using the Z test because the sample> 20. The results obtained from the results of the U Test namely Zhitung = 5.81 and at a significance level of 5%, obtained Ztable = 1.65. So it is obtained Zhitung> Ztabel so accept Ha. Thus, it can be concluded that learning outcomes of students taught with Problem Based Learning (PBL) are better than Contextual Teaching and Learning (CTL) in Geography Class X in SMAN 5 Banda Aceh